Postthrombotic syndrome and quality of life after deep vein thrombosis in patients treated with edoxaban versus warfarin. Issue 5 (1st July 2022) - Bistervels, Ingrid M.; Bavalia, Roisin; Beyer‐Westendorf, Jan; ten Cate‐Hoek, Arina J.; Schellong, Sebastian M.; Kovacs, Michael J.; Falvo, Nicolas; Meijer, Karina; Stephan, Dominique; Boersma, Wim G.; ten Wolde, Marije; Couturaud, Francis; et al.
Abstract: Background: Postthrombotic syndrome (PTS) is a long‐term complication after deep vein thrombosis (DVT) and can affect quality of life (QoL). Pathogenesis is not fully understood but inadequate anticoagulant therapy with vitamin K antagonists is a known risk factor for the development of PTS. Objectives: To compare the prevalence of PTS after acute DVT and the long‐term QoL following DVT between patients treated with edoxaban or warfarin. Methods: We performed a long‐term follow‐up study in a subset of patients with DVT who participated in the Hokusai‐VTE trial between 2010 and 2012 (NCT00986154). Primary outcome was the prevalence of PTS, defined by the Villalta score. The secondary outcome was QoL, assessed by validated disease‐specific (VEINES‐QOL) and generic health‐related (SF‐36) questionnaires. Results: Between 2017 and 2020, 316 patients were enrolled in 26 centers in eight countries, of which 168 (53%) patients had been assigned to edoxaban and 148 (47%) to warfarin during the Hokusai‐VTE trial. Clinical, demographic, and thrombus‐specific characteristics were comparable for both groups. Mean (SD) time since randomization in the Hokusai‐VTE trial was 7.0 (1.0) years. PTS was diagnosed in 85 (51%) patients treated with edoxaban and 62 (42%) patients treated with warfarin (adjusted odds ratio 1.6, 95% CI 1.0–2.6). Mean differences in QoL scores between treatment groups were not clinically relevant. Conclusion: Contrary to our hypothesis, the prevalence of PTS tended to be higher in patients treated with edoxaban compared with warfarin. No differences in QoL were observed. Further research is warranted to unravel the role of anticoagulant therapy on development of PTS.